Activation of caspase-9 and its influencing factors in beef during conditioning. (5th December 2013) - Cao, J.; Zhou, G.; Liu, Y.; Liao, G.; Zhang, Q.; Ye, K.; Pan, D.; Ou, C.
<x content-type="archive" xml:space="preserve">Abstract</x> To study the activation of caspase-9 and its potential influence in conditioning, longissimus thoracis (LT), semitendinosus (STN) and psoas minor (PMi) muscles were used to analyze the ratio of pro-apoptotic bax to anti-apoptotic bcl-2 in fresh tissues and observe the changes in ATP, cytosolic cytochrome c and caspase-9 activity levels during storage at 4°C. Caspase-9 activity at 5 h is higher than the activity at 0 and 24 h in the muscles (P<0.001). The ATP content decreased between 0 and 3 h, between 8 and 14 h in the PMi and LT muscles (P<0.0001), whereas between 0 and 5 h, between 8 and 14 h in the STN muscle (P<0.0001). There is 60.2%, 55.3% and 43.1% available ATP in the STN, LT and PMi muscles at 5 h, respectively. The cytosolic cytochrome c level increased during 5 and 24 h storage in the LT and PMi muscles (P<0.0001), during 5 and 96 h in the STN muscle (P<0.0001). The cytosolic cytochrome c at 24 h (P<0.001) and ratio of bax to bcl-2 (P<0.05) was higher in the PMi than in other muscles. We concluded that the increase in cytosolic cytochrome c and available intracellular ATP should be responsible for the increase in caspase-9 activity; the activation of caspase-9 could be limited by the subsequent depletion of ATP; the postmortem release level of cytochrome c could be determined by the ratio of bax to bcl-2 in fresh tissues.